2009
DOI: 10.1007/s00262-009-0695-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological evaluation of personalized peptide vaccination in combination with UFT and UZEL for metastatic colorectal carcinoma patients

Abstract: To investigate the safety and immunological responses of personalized peptide vaccination in combination with oral administration of UFT and UZEL for metastatic colorectal carcinoma (mCRC), fourteen patients were enrolled in the present study. Peptides were determined based on the presence of peptide-specific cytotoxic T lymphocyte precursors and IgG in each patient. A maximum of four peptides were subcutaneously administered weekly with UFT (300 mg/m2 day(-1)) and UZEL (75 mg/day) for 4 weeks, followed by 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
2
52
0
Order By: Relevance
“…To date, phase I cancer immunotherapy clinical studies that targeted the WT1 protein have been conducted for AML, MDS, lung, and breast cancer (22,23,31) and phase I/II clinical studies using WT1 peptides have been conducted for patients with various types of cancer (29). It was reported that the increase in the numbers of WT1-specific CTLs in cancer patients after vaccination with WT1 peptides closely correlates with the therapeutic efficacy against cancer (7,16,17,20). Therefore, monitoring antitumor immune responses, particularly the generation of tumor-specific CTLs, is critical for accurate assessments of the efficacy of cancer vaccine immunotherapy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, phase I cancer immunotherapy clinical studies that targeted the WT1 protein have been conducted for AML, MDS, lung, and breast cancer (22,23,31) and phase I/II clinical studies using WT1 peptides have been conducted for patients with various types of cancer (29). It was reported that the increase in the numbers of WT1-specific CTLs in cancer patients after vaccination with WT1 peptides closely correlates with the therapeutic efficacy against cancer (7,16,17,20). Therefore, monitoring antitumor immune responses, particularly the generation of tumor-specific CTLs, is critical for accurate assessments of the efficacy of cancer vaccine immunotherapy.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that cancer vaccine therapy with short peptides induces increased cancer antigen-specific CTLs and maintains long stable disease in the cancer patients. However, vaccine therapy using short peptides still has numerous issues that need to be resolved for treating cancers (7,27,28). Thus, it is necessary to develop more efficient cancer vaccines and establish accurate methods to evaluate cancer antigen-specific immune responses in patients.…”
mentioning
confidence: 99%
“…The number of administered vaccinations varied widely, from 3 to 112 per patient, with the most prolonged vaccination periods being for the prostate cancer patients. Most of the safety, immune, as well as clinical responses in these studies have been previously reported (5)(6)(7)(8)(9)(10)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Studies are currently underway to obtain vaccination results for the treatment of pancreatic and breast cancer, as well as for the HLA-A3 supertype-positive patients.…”
Section: Methodsmentioning
confidence: 99%
“…We developed a new approach of peptide-based vaccination, named personalized peptide vaccination (PPV), in which vaccine antigens are selected and administered based on preexisting host immunity before vaccination (6)(7)(8)(9)(10)(11)(12)(13)(14). We have shown promising results of PPV in various types of advanced cancers (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…We have shown promising results of PPV in various types of advanced cancers (6)(7)(8)(9). For example, a recently conducted randomized clinical trial of PPV for patients with advanced prostate cancer suggested a potentially favorable clinical outcome in the vaccinated group (9).…”
Section: Introductionmentioning
confidence: 99%